Bioactive hybrid metal-organic framework (MOF)-based nanosensors for optical detection of recombinant SARS-CoV-2 spike antigen - Rabiee, Navid; Fatahi, Yousef; Ahmadi, Sepideh; Abbariki, Nikzad; Ojaghi, Amirhossein; Rabiee, Mohammad; Radmanesh, Fatemeh; Dinarvand, Rassoul; Bagherzadeh, Mojtaba; Mostafavi, Ebrahim; Ashrafizadeh, Milad; Makvandi, Pooyan; et al. (The Science of the total environment, 2022)
Fast, efficient, and accurate detection of SARS-CoV-2 spike antigen is pivotal to control the spread and reduce the mortality of COVID-19. Nevertheless, the sensitivity of available nanobiosensors to detect recombinant SARS-CoV-2 spike antigen seems insufficient. As a proof-of-concept, MOF-5/CoNi2S4 is developed as a low-cost, safe, and bioactive hybrid nanostructure via the one-pot high-gravity protocol. Then, the porphyrin, H2TMP, was attached to the surface of the synthesized nanomaterial to increase the porosity for efficient detection of recombinant SARS-CoV-2 spike antigen. AFM results approved roughness in different ranges, including 0.54 to 0.74 μm and 0.78 to ≈0.80 μm, showing good physical interactions with the recombinant SARS-CoV-2 spike antigen. MTT assay was performed and compared to the conventional synthesis methods, including hydrothermal, solvothermal, and microwave-assisted methods. The synthesized nanodevices demonstrated above 88% relative cell viability after 24 h and even 48 h of treatment. Besides, the ability of the synthesized nanomaterials to detect the recombinant SARS-CoV-2 spike antigen was investigated, with a detection limit of 5 nM. The in-situ synthesized nanoplatforms exhibited low cytotoxicity, high biocompatibility, and appropriate tunability. The fabricated nanosystems seem promising for future surveys as potential platforms to be integrated into biosensors. [Display omitted] •One-pot synthesis of MOF-5/CoNi2S4 in assistance of high-gravity•Turning a toxic cobalt‑nickel-based nanoparticle into a non-toxic form•Highly sensitive recombinant SARS-CoV-2 spike antigen optical biosensor